1967
DOI: 10.1080/00288233.1967.10426364
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of “Grasslands Ariki” and “Grasslands Ruanui” ryegrasses for lamb fattening in Southland

Abstract: Experiments in spring and autumn comparing the growth of lambs on "Grasslands Ariki" and "Grasslands Ruanui" ryegrasses in association with white clover at Gore are described.In spring no difference in growth late or meat yield was detectable. In autumn growth rate was highest for animals on Ariki.The effects of set stocking, rotational grazing, and selenium dosing are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1973
1973
1994
1994

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Ariki is a persistent hybrid ryegrass with a wide seasonal spread of production (Barclay 1963;Lancashire et al 1979). Harris & Johnston (1967, during a series of animalfattening experiments in Southland, likewise confirmed Ariki's superior performance resulting in improved liveweight gains in lambs compared with 'Grasslands Nui' perennial ryegrass (L. perenne L.). This result has lately been confirmed by Fletcher (1986) in a comparative ryegrass endophyte (Acremonium) experiment conducted in Canterbury.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Ariki is a persistent hybrid ryegrass with a wide seasonal spread of production (Barclay 1963;Lancashire et al 1979). Harris & Johnston (1967, during a series of animalfattening experiments in Southland, likewise confirmed Ariki's superior performance resulting in improved liveweight gains in lambs compared with 'Grasslands Nui' perennial ryegrass (L. perenne L.). This result has lately been confirmed by Fletcher (1986) in a comparative ryegrass endophyte (Acremonium) experiment conducted in Canterbury.…”
Section: Introductionmentioning
confidence: 51%
“…In terms of lamb production at Gore, Hickey & Baxter (1989) have demonstrated the advantage of winter feeding of Moata compared with Nui, whereas 'Grasslands Ariki' hybrid ryegrass is advantageous in autumn compared with 'Grasslands Ruanui' perennial ryegrass (Harris & Johnston 1967. However, cultivar variation in terms of measurable animal performance (e.g., Wilson 1968;Ulyatt 1971) between closely related species of ryegrass may be difficult to demonstrate particularly for dairy production (e.g., Wilson & Dolby 1967;McCallum & Thomson 1994).…”
Section: Total Herbage Productionmentioning
confidence: 99%
“…There were two stocking rates in spring and three in autumn. These rates and the duration of the trial, were as follows: Huia' white clover) and grazed as reported pre-Sub-plot size was 0.27 ha for the low rate and viously (Harris & Johnston 1967). 0.13 ha for the high rate in spring, and in autumn The experiment was in two parts in each of 2 each sub-plot was 0.13 ha.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work on evaluation of ryegrass varieties using sheep (Harris & Johnston 1967) pointed to the difficulties inherent in a technique where only one stocking rate was used, and suggested that the most acceptable method appeared to be assessment of animal weight changes at various stocking rates.…”
Section: Introductionmentioning
confidence: 99%
“…During autumn, New Zealand workers have reported increases of the order of 18% more meat/ ha from cv. Grasslands Ariki ryegrass (an Italian ryegrass-perennial ryegrass hybrid) compared to perennial ryegrass (Harris & Johnston 1967). Italian ryegrass has increased milk production in winter by 17% when compared to perennial ryegrass (Wilson & Dolby 1967).…”
Section: Cultivars With Contrasting Soluble:structural Carbohydrate Rmentioning
confidence: 99%